On the Diversity of Linguistic Data and the Integration of the Language Sciences - D’Alessandro, Roberta; van Oostendorp, Marc (Frontiers in Psychology, 2017)
An integrated science of language is usually advocated as a step forward for linguistic research. In this paper, we maintain that integration of this sort is premature, and cannot take place before we identify a common object of study. We advocate instead a science of language that is inherently multi-faceted, and takes into account the different viewpoints as well as the different definitions of the object of study. We also advocate the use of different data sources, which, if non-contradictory, can provide more solid evidence for linguistic analysis. Last, we argue that generative grammar is an important tile in the puzzle.